[PP.04.11] REGULATORY T CELLS AND CELLS PRODUCING CYTOKINES IN CHILDREN WITH PRIMARY HYPERTENSION. (September 2016) - Obrycki, L.; Gackowska, L.; Niemirska, A.; Kubiszewska, I.; Klosowski, M.; Michalkiewicz, J.; Litwin, M.
Abstract : Objective: The aim of the study was to evaluate the percentage of regulatory T cells (Tregs) and cells producing cytokines (IL-17, IFN-gamma and TNF-alpha) in children with primary hypertension (PH). Design and method: The peripheral whole blood samples were obtained from PH patients and normotensive, healthy children. T-cell subtypes were defined by the combinations of cell surface markers and antibodies against intracellular cytokines they secrete (IL-17, IFN-gamma, TNF-alpha). For enumeration of Tregs (CD4+/CD25+/CD127-) and cytokines-producing cells conjugated monoclonal antibodies were used in direct method. Leukocyte adiponectin receptor expression (AdipoR1) was determined using direct and indirect three-color flow cytometry. After having compared immunological parameters between children with PH and normotensive ones, patients were divided into two groups, based on the AdipoR1 expression: patients exhibiting high expression [AdipoR1(+)] and children with a low expression [AdipoR1(−)] of the test marker on leukocytes. Results: Children with PH had greater percentage of Tregs (8.33 ± 1.84 vs. 7.45 ± 1.77) and cells producing proinflammatory cytokines (IL-17+:3.51 ± 1.75 vs. 1.57 ± 0.75; IFN-gamma+:3.68 ± 1.72 vs. 2.23 ± 0.84; TNF-alpha+:3.38 ± 1.66 vs. 2.28 ± 1.16; p < 0.05). AdipoR1(−) PH patients showed greater percentage of Tregs (9.45 ± 1.81) than AdipoR1(+) PH patients (7.35 ± 1.22) and normotensive ones (7.45 ± 1.77) (p < 0.001). The percentage of Tregs did not differ between the AdipoR1(+) group and the control group (p = 0.8). The highest proportion of proinflammatory cells was found in AdipoR1(−) group (IL-17+: 4.76 ± 1.77, IFN-gamma+: 4.25 ± 2.06) versus AdipoR1(+) group (IL-17+: 2.47 ± 0.81, IFN-gamma+: 3.20 ± 1.24) of PH patients (in all cases p < 0.001). The percentage of cells producing TNF-alpha was significantly higher in both groups of patients (3.07 ± 0.94 and 3.78 ± 2.28) compared to the control (2.29 ± 1.16; p < 0.05). Conclusions: Our results indicate that children with PH have greater percentage of Tregs and cells producing cytokines than normotensive ones. We also observed that decreased AdipoR1 expression may limit leukocyte responsiveness to adiponectin. This in turn may increase synthesis of proinflammatory cytokines IL-17 and IFN-gamma. These observations are an argument for the significance of adipose tissue and adipokines in the regulation of inflammatory responses in hypertensive children. T-regulatory cells can limit inflammatory response and therefore prevent tissue damage (in this case – arteriolar walls, which leads to hypertension) as was previously described.